Climatic variability and cooperation in rangeland management: a case study from Niger - McCarthy, Nancy; Vanderlinden, Jean-Paul (International Food Policy Research Institute, 2002)
In this paper, we develop an empirical model of an agro-pastoral system subject to high climatic risk to test the impact of rainfall variability on livestock densities, land allocation patterns and herd mobility observed at the community level. Also, because grazing land is a common-pool resource, we determine the impact of cooperation on these decision variables. To capture different abilities of communities to manage these externalities, we construct indices comprised of factors considered to affect the costliness of achieving successful cooperation found in the collective action literature. We then test hypotheses regarding the impact of rainfall variability and cooperation using data collected in a semi-arid region of Niger. Results indicate that rainfall variability first leads to higher and then lower stock densities, indicating that benefits of accumulating large herds in variable environments are eventually offset by the higher risks of low production and higher mortality. Communities with characteristics hypothesized to favor cooperation have lower stock densities and greater herd mobility. Neither cooperation nor rainfall variability has a significant impact on the proportion of land allocated to crops vs. common pastures.